2000
DOI: 10.1034/j.1399-6576.2000.440713.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of an epidural analgesic solution containing adrenaline, bupivacaine and fentanyl

Abstract: The triple-component epidural analgesic solution remained stable during six months of cold storage, followed by four days of storage at room temperature. No significant degradation of adrenaline was observed in infusion solutions returned from the wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…We also found a smaller fall in epinephrine concentration (7.4% loss) and pH (4.31-4.18) at room temperature over 180 days, with no visible discoloration of the solution, perhaps due to the lower concentrations of epinephrine used in this study. Our findings are in accordance with those of Kjonniksen and coworkers [8], who studied the stability of the solution described by Niemi and Breivik [2], i.e. fentanyl (2 lg.ml )1 ), bupivacaine (1 mg.ml )1 ) in PVC bags and epinephrine (2 lg.ml )1 ) stored at 2-8°C for 180 days and then 22°C for a further 4 days.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found a smaller fall in epinephrine concentration (7.4% loss) and pH (4.31-4.18) at room temperature over 180 days, with no visible discoloration of the solution, perhaps due to the lower concentrations of epinephrine used in this study. Our findings are in accordance with those of Kjonniksen and coworkers [8], who studied the stability of the solution described by Niemi and Breivik [2], i.e. fentanyl (2 lg.ml )1 ), bupivacaine (1 mg.ml )1 ) in PVC bags and epinephrine (2 lg.ml )1 ) stored at 2-8°C for 180 days and then 22°C for a further 4 days.…”
Section: Discussionsupporting
confidence: 92%
“…For this to occur, stability data for the admixture are required. While stability data have been published for solutions containing epinephrine with fentanyl and bupivacaine from around the world [7][8][9], for a number of reasons these data are not transferable to UK practice, as described below. We therefore undertook this study to determine whether an admixture containing epinephrine (2 lg.ml )1 ), fentanyl (2 lg.ml )1 ) and bupivacaine (1 mg.ml )1 ) was stable using agents readily available to UK hospital pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…The HPLC methods were based on previously published methods, which were modified and their ability to monitor stability was evaluated during validation studies. Briefly, an Agilent Technologies 1100 HPLC system (Agilent Technologies Inc., Waldbronn, Karlsruhe, Germany) employing a binary pump, micro‐vacuum degasser, autosampler, thermostatted column compartment, diode array detector, fluorescent detector and Agilent Technologies Chemstation ® for LC 3D Software (Rev.…”
Section: Methodsmentioning
confidence: 99%
“…Optimal separation of fentanyl citrate and bupivacaine hydrochloride is possible at 15%–40% concentration of the organic component in the mobile phase. It is suggested that the inorganic component should have pH ≤ 5 813. UV detection at λ=210 nm was selected as it is the absorbance maximum for fentanyl citrate present in the solution at a concentration 200 times lower than that of bupivacaine hydrochloride, which poses a considerable analytical problem.…”
Section: Resultsmentioning
confidence: 99%